Dislodgement force and shell morphology vary according to wave exposure in a tropical gastropod (Cittarium pica). Issue 9 (20th October 2016) - Forrester, Graham E.; Macfarlan, Reuben J. A.; Holevoet, Allison J.; Merolla, Sarah
ABSTRACT: Wave exposure has strong influences on population density, morphology and behaviour of intertidal species in temperate zones, but little is known about how intertidal organisms in tropical regions respond to gradients in wave exposure. We tested whether dislodgement force and shell shape of a tropical gastropod, Cittarium pica, differs among shores that vary in wave exposure. After adjusting for body size, we found that C. pica from exposed shores required greater dislodgement force to remove them from the shore, had slightly larger opercula (the closure to the shell aperture), and were slightly squatter in shape (reduced in shell height relative to shell width) than C. pica from sheltered shores. These morphological adjustments are consistent with those observed in temperate gastropods, which are argued to represent adaptive responses to the risk of mortality associated with dislodgement.